Accuracy of Predictions of Patients With Breast Cancer of Future Well-being After Immediate Breast Reconstruction - Lee, Clara Nan-hi (JAMA Surg, 2018)
IMPORTANCE: Making a good decision about breast reconstruction requires predicting how one would feel after the procedure, but people tend to overestimate the impact of events on future well-being. OBJECTIVE: To assess how well patients predict future well-being after mastectomy, with or without immediate reconstruction, with the following a priori hypotheses: Patients will overestimate the negative impact of mastectomy and positive impact of reconstruction, and prediction accuracy will be associated with decision satisfaction and decision regret. DESIGN, SETTING, AND PARTICIPANTS: This prospective cohort survey study was conducted at a single, multidisciplinary academic oncology clinic from July 2012 to February 2014. Adult women undergoing mastectomy for stage 1, 2, or 3 invasive ductal or lobular breast cancer, ductal carcinoma in situ, or prophylaxis were invited to participate. Data analysis was conducted from September 2015 to October 2017. EXPOSURES: Mastectomy only or mastectomy with immediate reconstruction. MAIN OUTCOMES AND MEASURES: Preoperative measures predicted were 12-month happiness (Cantril Ladder) and quality of life, predicted satisfaction with breasts, sexual attractiveness, breast numbness, and pain (measured with BreastQ single items). Measures at 12 months postoperative added the Decision Regret Scale and Satisfaction With Decisions Scale. RESULTS: Of 214 eligible patients, 182 consecutive patients were approached, and 145 enrolled (80%). Of these 145 patients, 131 returned surveys (72%) and 111 of these remained at 12 months (88%). Fifteen who had delayed reconstruction were excluded from analysis, leaving a final cohort of 96 women; 54 had not had reconstruction and 42 had had reconstruction. The mean (SD) age of the cohort was 53.9 (12.1) years; 73 (76%) were white; 50 (52%) were college graduates; 54 (56%) were privately insured; 69 (72%) had disease at stages 0, 1, or 2; and 31 (32%) received adjuvant radiation. Patients having mastectomy without reconstruction underestimated future well-being in all domains. Differences were significant for quality of life scores (mean predicted, 68 vs mean actual, 74; t(50), −2.47; P = .02) and satisfaction with breasts–clothed (mean predicted, 2.4 vs mean actual, 2.8; t(49), −2.11; P = .04). Patients undergoing mastectomy with reconstruction overestimated future well-being in all but 1 domain. Differences were significant for satisfaction with breasts–unclothed (mean predicted, 3.1 vs mean actual, 2.6; t(41), 2.70; P = .01); sexual attractiveness–clothed (mean predicted, 3.7 vs mean actual, 3.3; t(39), 2.29; P = .03); sexual attractiveness–unclothed (mean predicted, 3.3 vs mean actual, 2.3; t(40), 5.57; P < .001). Both groups experienced more numbness than predicted (mean predicted, 2.79 and 2.72 for mastectomy only and mastectomy with reconstruction groups, respectively; mean actual, 3.52 and 3.56, respectively; t(47), −3.4 and t(38), −2.9, respectively; P < .01). Patients who were less happy (β = 6.3; P = .02) or had greater pain (β = 8.7; P < .001) than predicted had greater regret. CONCLUSIONS AND RELEVANCE: Patients underestimated future well-being after mastectomy and overestimated well-being after reconstruction. Misprediction was associated with regret. Decision support for breast reconstruction should address expectations about well-being.